2006
DOI: 10.1021/ic051518c
|View full text |Cite
|
Sign up to set email alerts
|

Coarse and Fine Tuning of the Electronic Energies of Triimineplatinum(II) Square-Planar Complexes

Abstract: [Pt(tbtrpy)X]Y complexes (tbtrpy = 4,4',4' '-tBu3-2,2';6',2' '-terpyridine) exhibit charge-transfer absorption bands that can be drastically red-shifted to long-wavelength visible absorptions with arylthiolates as X. Further extension to the near-IR (NIR) region is achieved with 7,7,8,8-tetracyanoquinodimethane (TCNQ-) as Y-, resulting in black absorbers with continuous UV-vis-NIR absorptions and opening up potential applications in energy research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(58 citation statements)
references
References 22 publications
(33 reference statements)
6
52
0
Order By: Relevance
“…Chen et al 134 reported unique black absorbers with continuous UV-vis-NIR absorptions by simply changing the counterion and the co-ligand of the [Pt(t-Bu 3 -tpy)(Cl)][Cl] to [Pt(t-Bu 3 -tpy)(R-PhS)][TCNQ] complexes (TCNQ ) 7,7,8,8-tetracyano-quinodimethane; R ) 4-Me, 4-Cl, 3,4-diMe, and 2,5-diOMe) for possible conducting, magnetic, and solar cell applications. The crystal structure of 108 revealed short-range π-π interactions between Pt(II) cation and TCNQ anion with interplanar distances of 3.5 Å ( Figure 48A).…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…Chen et al 134 reported unique black absorbers with continuous UV-vis-NIR absorptions by simply changing the counterion and the co-ligand of the [Pt(t-Bu 3 -tpy)(Cl)][Cl] to [Pt(t-Bu 3 -tpy)(R-PhS)][TCNQ] complexes (TCNQ ) 7,7,8,8-tetracyano-quinodimethane; R ) 4-Me, 4-Cl, 3,4-diMe, and 2,5-diOMe) for possible conducting, magnetic, and solar cell applications. The crystal structure of 108 revealed short-range π-π interactions between Pt(II) cation and TCNQ anion with interplanar distances of 3.5 Å ( Figure 48A).…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…It can be speculated that the molecules are packed more closely in Form-H than in Form-M, therefore they induce a stronger donor-toacceptor charge transfer interaction and result in further absorption into the near-IR region. 47,48 Other than the differences in color and absorption, a distinct difference in the degree of crystallinity is observed between the two solid species (Fig. 2).…”
Section: Synthesis and Characterizationmentioning
confidence: 94%
“…S1 †), which is the characteristic absorption of the TCNQc À anion. [38][39][40][41][42]47 Additionally, EPR spectra have been measured, and the g-factors of Form-M (g ¼ 2.003) and Form-H (g ¼ 2.004) are almost the same (Fig. S2 †), which is attributed to the unpaired electron of the TCNQc À radical anion.…”
Section: Synthesis and Characterizationmentioning
confidence: 97%
See 2 more Smart Citations